Etiology of thumb sucking habit and its effect on developing malocclusion - Ahmed, Zahid Nisar; Hussin, Ahmed Mahmoud; Alanazi, Anoud Fahad; Alhuraish, Abdullah Mohammed; Abomelha, Sarah Abdullah; Tulbah, Thabt Hassan; Alshahrani, Aidel Abdullah; Alotaibi, Alanoud Fahad; Alkheshail, Walaa Amer; Almalki, Waleed Khalid; Alshaikh, Waed Shaker; Aldossari, Ali Mohammed (International Journal Of Community Medicine And Public Health, 2021)
The persistence of thumb sucking might also be harmful as it might be associated with the development of complications seen on the thumb as paronychia and nail deformities and in the mouth level as malocclusions. In this review, we have looked up studies in the literature to identify the effect of thumb sucking on the development of malocclusion. Thumb sucking in children usually occurs as a primitive reflex that appears in early childhood with no apparent causative factors. Children usually develop this thumb sucking habit because in this way they feel more comfortable and secure. The main cause behind the development of thumb sucking is the prolonged presence of the thumb in the mouth which creates pressure against the developing jaw and teeth. This may interfere with the process of tooth eruption leading to delayed or abrupt eruption events and malformations. The severity of malocclusion deformities is significantly associated with the chronicity and period of thumb-sucking habits. Other forms of occlusions secondary to thumb sucking include: anterior open bite, exaggerated overjet, posterior crossbite, retrognathic mandible, a diastema, temporomandibular joint disorders and the retroclined low anterior. Thumb sucking, however, is a self-limiting phenomenon and usually disappears as children grow older. However, when persistence is noticed, immediate management should be approached to avoid any potential complications.